Secondary queens in the parthenogenetic termite Cavitermes tuberosus develop through a transitional helper stage. Issue 6 (8th November 2017) - Hellemans, Simon; Fournier, Denis; Hanus, Robert; Roisin, Yves
Abstract : In termite species with asexual queen succession (AQS), parthenogenetically produced immatures mostly differentiate into secondary queens, called "neotenics." In order to elucidate the ontogenetic origin of neotenics in Cavitermes tuberosus (Termitidae: Termitinae), a neotropical termite with AQS, we investigated developmental pathways of offspring according to their sex and genetic origin using both morphometric and genetic tools. The caste system of C. tuberosus follows the classical pathway of Termitidae. After the first larval instar, there is a bifurcation between two developmental lines. The apterous line is composed of a second larval instar, several worker instars, presoldiers, and soldiers. Workers display a consistent male bias and soldiers are female‐only. The nymphal line is composed of five nymphal instars and the imago stage. We highlight that neotenic queens derive from third and fourth instar nymphs displaying peculiar morphological traits, here termed "aspirants, " most of which are produced by parthenogenesis. Aspirants are present in all nests and perform worker tasks while waiting for the queen's death to differentiate into neotenic queens. Aspirants can successfully be used to demonstrate the occurrence of parthenogenesis in termite species whose reproductive cores are difficult to access.